2018
DOI: 10.1021/acsomega.8b01103
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonic Acid-Functionalized Cross-Linkers to Tailor Hydrogel Properties for Biomedical Applications

Abstract: Two bisphosphonic acid-functionalized cross-linkers (one novel) with different spacer chain characteristics were synthesized and incorporated into hydrogels by copolymerization with 2-hydroxyethyl methacrylate at different ratios to control the hydrogels’ swelling, mechanical properties, and ability to support mineralization for biomedical applications. The cross-linkers were synthesized by reaction of 2-isocyanatoethyl methacrylate and bisphosphonated diamines followed by selective dealkylation of the bisphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…The interaction between phosphonic acid groups and Ca 2+ ions may form physical crosslinking. 18,19 However, it was observed that phosphonic acid content in the hydrogel needs to reach a certain level to This article is protected by copyright. All rights reserved.…”
Section: Swelling and Degradation Studies Of The Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between phosphonic acid groups and Ca 2+ ions may form physical crosslinking. 18,19 However, it was observed that phosphonic acid content in the hydrogel needs to reach a certain level to This article is protected by copyright. All rights reserved.…”
Section: Swelling and Degradation Studies Of The Hydrogelsmentioning
confidence: 99%
“…13 It is well known that negatively charged groups such as the phosphate, (bis)phosphonate, carboxylate, sulfonic group on surfaces of hydrogels act as nucleating centers for the deposition of hydroxyapatite-like calcium phosphate and enhance mineralization which is a fundamental step for bone regenaration. [14][15][16][17][18][19][20] Additionally, phosphorous based groups promote cell adhesion and osteogenic differentiation. [21][22][23][24] Liu et al synthesized alendronate functionalized methacryloyl gelatin and observed upregulation of the osteogenesis-related genes as well as improvement in mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Among various biomaterials, hydrogels that share many properties with soft tissue have become a research hotspot (Xue et al, 2019). Many types of hydrogels have been researched in dermal wound healing, such as bisphosphonate-functionalized hydrogel (Guven et al, 2018), chitosan hydrogel (Ponsubha and Jaiswal, 2020) and thermoresponsive hydrogel (Zhu et al, 2016). However, none of these materials allow for stable biological fixation, which is crucial in constructing the wound barrier and maintaining the applied agent (Dreifke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphonate-chitosan functionalization of a multichannel hydroxyapatite scaffolds have been utilized for interfacial implant-bone tissue integration with the enhancement of new bone formation. [15] Further with phosphnated materials, the bioactive coatings consisting of phosphonated molecules and zirconia have been also designed for bone implants. [15] Although PEEK based polymers have been tried previously for dental and bone implants, however, modification of the PEEK chain can result in several issues such as non-uniform degree of modification and a compromise in the excellent properties of PEEK.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Further with phosphnated materials, the bioactive coatings consisting of phosphonated molecules and zirconia have been also designed for bone implants. [15] Although PEEK based polymers have been tried previously for dental and bone implants, however, modification of the PEEK chain can result in several issues such as non-uniform degree of modification and a compromise in the excellent properties of PEEK. [8,9,10] Hence, modification of the PEEK backbone may not be as an effective tool to design a bioactive homopolymer as compared to its block copolymer counterpart.…”
Section: Introductionmentioning
confidence: 99%